2020
DOI: 10.1038/s41598-020-60052-z
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and characterisation of ethanol chain elongating communities from natural and engineered environments

Abstract: chain elongation is a microbial process in which an electron donor, such as ethanol, is used to elongate short chain carboxylic acids, such as acetic acid, to medium chain carboxylic acids. this metabolism has been extensively investigated, but the spread and differentiation of chain elongators in the environment remains unexplored. Here, chain elongating communities were enriched from several inocula (3 anaerobic digesters, 2 animal faeces and 1 caproic acid producing environment) using ethanol and acetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 39 publications
0
15
2
Order By: Relevance
“…Possibly, a higher catabolic rate could not effectuate a higher growth rate at pH 7.0 because the culture was already growing at µ max . However, the average growth rate in our systems was 0.058 h −1 , which is significantly lower than µ max -values reported in literature (0.1-0.24 h −1 ) for C. kluyveri but comparable to growth rates (0.05-0.09 h −1 ) of communites enriched from anaerobic digester sludge in batch bottles (Weimer and Stevenson, 2012;Candry et al, 2018Candry et al, , 2020. Alternatively, faster growth might have been inhibited by relatively large amounts of fermentation products, leading to a trade-off between additional energy generation and maintaining endurable product concentrations.…”
Section: Caproic Acid Toxicity Steers the Balance Between Substrate Consumption And Product Inhibitioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Possibly, a higher catabolic rate could not effectuate a higher growth rate at pH 7.0 because the culture was already growing at µ max . However, the average growth rate in our systems was 0.058 h −1 , which is significantly lower than µ max -values reported in literature (0.1-0.24 h −1 ) for C. kluyveri but comparable to growth rates (0.05-0.09 h −1 ) of communites enriched from anaerobic digester sludge in batch bottles (Weimer and Stevenson, 2012;Candry et al, 2018Candry et al, , 2020. Alternatively, faster growth might have been inhibited by relatively large amounts of fermentation products, leading to a trade-off between additional energy generation and maintaining endurable product concentrations.…”
Section: Caproic Acid Toxicity Steers the Balance Between Substrate Consumption And Product Inhibitioncontrasting
confidence: 76%
“…This equaled an ethanol-to-acetate ratio of 6:1 in the bioreactor feed. A relatively high concentration of ethanol versus acetate was reported to positively influence caproate production (Liu et al, 2016) and a 6:1 ratio enabled both butyrate and caproate formation at pH 5.5 and pH 7.0 (Candry et al, 2020). Therefore, this feeding regime was chosen to allow for the characterization of the effect of both butyrate and caproate on chain elongating communities at different pH values.…”
Section: Reactor Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the selectivity of 2-BES comes with caveats. Recent studies indicated collateral effects of 2-BES addition on carboxylate production, such as inhibition of i- butyrate formation 6, 8 and an increase of sulfate-reducing bacterial populations, suggesting 2-BES degradation in the long term 911 . Moreover, application of 2-BES at the high concentrations (50 mM 12 ) needed to inhibit hydrogenotrophic methanogenesis (Equation 4) might be economically unfeasible in industrial scale.…”
Section: Introductionmentioning
confidence: 99%